2012
DOI: 10.1186/cc11463
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment in sepsis: a new prognostication rule by APACHE II score and serum soluble urokinase plasminogen activator receptor

Abstract: IntroductionEarly risk assessment is the mainstay of management of patients with sepsis. APACHE II is the gold standard prognostic stratification system. A prediction rule that aimed to improve prognostication by APACHE II with the application of serum suPAR (soluble urokinase plasminogen activator receptor) is developed.MethodsA prospective study cohort enrolled 1914 patients with sepsis including 62.2% with sepsis and 37.8% with severe sepsis/septic shock. Serum suPAR was measured in samples drawn after diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
1
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 23 publications
6
83
1
12
Order By: Relevance
“…Among the 17 eligible studies, 9 studies including 1237 patients reported the usefulness of suPAR for diagnosing infections131415161718192021, and 10 studies including 3041 patients reported its usefulness for predicting mortality14212223242526272829. The characteristics of the studies are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 17 eligible studies, 9 studies including 1237 patients reported the usefulness of suPAR for diagnosing infections131415161718192021, and 10 studies including 3041 patients reported its usefulness for predicting mortality14212223242526272829. The characteristics of the studies are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 4 studies investigated the diagnostic value of suPAR in differentiating sepsis from SIRS16192021. Of the 10 studies reporting the value of suPAR in predicting mortality, 7 recruited patients suffering from sepsis14212526272829, and 3 recruited patients with bacteremia222324. The serum level of suPAR was measured using an enzyme-linked immunosorbent assay kit (ViroGates, Birkerød, Denmark) in most of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that total suPAR levels correlate with CRP levels in conditions of inflammation. 32 Systemic inflammation and/or change in renal function as potential confounders can be excluded in our study as median CRP levels remained low and baseline-creatinine did not change significantly during the full course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on 454 critically patients receiving ventilatory support showed that suPAR levels were slightly higher in patients that died or developed acute kidney failure 87 . In another large study with 1914 patients with sepsis, suPAR levels >12 ng/ml were associated with an unfavorable outcome, especially in patients with an APACHE II score >17 88 . suPAR does not, as yet, have a role as a biomarker for sepsis diagnosis.…”
Section: Biomarkersmentioning
confidence: 99%